iPad For Dummies, 8th Edition - Baig, Edward C. (Office Essentials collection, 2016)
Ultraportable and powerful, the latest iPad model is brimming with features and functions you'll be eager to explore. This straightforward, yet fun book provides and approachable resource that covers everything you'll need to know to operate your iPad with ease. --